The first case of surgical myocardial revascularization and endarterectomy of the right carotid artery in the same procedure in a patient with haemophilia A - Janković, Nataša; Dragan, Simić; Mikić, Aleksandar; Matković, Miloš; Vukičević, Petar; Elezović, Ivo (Vojnosanitetski pregled, 2021)
Introduction. Haemophilia A is the most common hereditary coagulation disturbance occurring due to the lack of coagulation factor VIII. It is widely accepted that people with haemophilia have a reduced incidence of coronary artery disease, potentially because of the protective effect of the impaired coagulation against the pathogenic mechanisms of the acute coronary syndrome. Case report. A 53-year-old man with mild haemophilia [FVIII 22% (mild form: more than 5%–40% of normal)] was hospitalized because of frequent anginal pain at rest. Selective coronary angiography revealed a severe three-vessel coronary disease. A need for urgent surgical revascularization was indicated. The color duplex scan showed the existence of hemodynamically significant stenosis on the right internal carotid artery. After consulting a haematologist, a cardiac surgeon, and a vascular surgeon, it was concluded that due to high bleeding risk, the patient should undergo an endarterectomy of the right carotid artery and a triple aortocoronary bypass in the same procedure. Procedures were performed with a substitution of FVIII concentrate. The patient firstly underwent the endarterectomy of the right carotid artery. Then, the left mammary artery graft was implanted to the left anterior descending artery as well as the venous grafts to the first obtuse marginal artery and posterior descending branch. There were no complications. During the revascularization, there was no need for blood transfusion, nor was there excessive bleeding in the postoperative period. The patient was discharged with antithrombotic therapy (aspirin, 50 mg). Conclusion. Patients with haemophilia are not protected against the development of atherosclerosis. Cardiac surgery in these patients presents a unique challenge for medical teams in securing haemostasis. Adequate substitution with factor VIII concentrate provides adequate haemostasis and the possibility for treatment with antiplatelet therapy.
Keywords: hemophilia a; coronary disease; coronary artery bypass; endarterectomy, carotid; cardiovascular surgical procedures; treatment outcome